(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Over the past 50 years, there has been a marked increase in the number of divorces in most Western societies. The breakdown of relationships is associated with negative consequences for both adults and children, so it is important to understand the factors that help maintain family stability. Prospective studies conducted in Norway in over 18,000 thousand couples experiencing relationship difficulties were reviewed, and the effects of interaction between relationship dissatisfaction and other predictors of marriage breakup were also considered. At the end of the scientific article, conclusions will be given on the comparison of problems with divorces in Norway with Uzbekistan.